2014
DOI: 10.1007/s13197-014-1424-5
|View full text |Cite
|
Sign up to set email alerts
|

The process of producing tomato paste by ohmic heating method

Abstract: In this study, the effect of ohmic heating technique on electrical conductivity, water evaporation rate, heating rate, colour parameters, pH and energy consumption of tomato samples was investigated. Ohmic heating was accomplished till the moisture content of the tomato samples reduced from initial moisture content of as 9.33 (dry basis) to a safer level of 2.2. The results of the nonlinear mathematical model including the effects of voltage gradient level and the temperature on the electrical conductivity cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…This phenomenon was since the heat generation by OH was directly proportional to the square of voltage applied and the EC of food (Cappato et al, 2017). Both EC and temperature increased during OH treatment, mainly due to the structural changes of the meat tissues and the increased ionic mobility at higher temperatures (Boldaji, Borghei, Beheshti, & Hosseini, 2015;Guo et al, 2017;Llave, Morinaga, Fukuoka, & Sakai, 2018;Marra, Zell, Lyng, Morgan, & Cronin, 2009). This characteristic associated with OH might make it more effective at high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was since the heat generation by OH was directly proportional to the square of voltage applied and the EC of food (Cappato et al, 2017). Both EC and temperature increased during OH treatment, mainly due to the structural changes of the meat tissues and the increased ionic mobility at higher temperatures (Boldaji, Borghei, Beheshti, & Hosseini, 2015;Guo et al, 2017;Llave, Morinaga, Fukuoka, & Sakai, 2018;Marra, Zell, Lyng, Morgan, & Cronin, 2009). This characteristic associated with OH might make it more effective at high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Ohmic heating has also been used to produce tomato paste. Boldaji, Borghei, Beheshti, and Hosseini (2015) found that ohmic heating at 14 V/cm was able to produce tomato paste without negatively affecting color parameters. Makroo Rastogi, and Srivastav (2017) investigated the effects of ohmic heat treatment on the enzyme inactivation in tomato juice and characteristics of the paste prepared from the treated juice and observed that PG and PME enzyme inactivation achieved in 1 min of ohmic heating at 90°C was similar to that of conventional hot water heating of 5 min at the same temperature.…”
Section: Ohmic Heatingmentioning
confidence: 97%
“…The use of the ohmic heating technique for the purpose of heating, pasteurization, sterilization of liquid foods (fruit‐vegetable juice, milk, liquid egg) has been allowed by some organizations such as the Food and Drug Administration (FDA) and the US Department of Agriculture (USDA) . However, studies on the utilization of ohmic heating as a heat source are limited in open literature . Assiry and Elansari applied atmospheric ohmic evaporation to concentrate date syrup from 27 ± 0.03 total soluble solid (TSS) to 70% TSS content.…”
Section: Introductionmentioning
confidence: 99%